Moral Teachings in Bugis Folktales - Dafirah; Pammuda; Andi Tenri Bali Baso (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
One important effort in developing character education based on local wisdom is the rediscovery and exploration of folktales that are scattered and preserved among ethnic groups throughout the Indonesian archipelago. The Bugis ethnic group is one of the communities that possesses a rich collection of folktales. Bugis folktales are traditional literary works born from the spiritual experiences and imagination of their creators. Nevertheless, these stories have also played a significant role in shaping the life journey of the Bugis people and humanity in general. More importantly, Bugis folktales are not merely traditional literary works but also serve as a source of moral teachings. Moral values such as honesty, perseverance, obedience, mutual respect and appreciation, mutual reminder, compassion, patience, and others can be found in various folktales. These moral messages have the potential to serve as references for character formation within the Bugis community and even for national character development. This study is expected to be beneficial for both the Bugis ethnic community and Indonesian society in general, particularly in the context of character formation based on local wisdom. Revealing the meanings and values embedded in each folktale is expected to contribute significantly to the development of character education.